Peningkatan Keterampilan Menulis Puisi Melalui Pendekatan Culturally Responsive Teaching Berbantuan Media Gambar Seri - Anggita Puji Lestari; Tri Wahyuningsih; Retno Winarni; Mei Iriana (Universitas Sebelas Maret, 2025)
This research is conducted to enhance students' ability in writing poetry through the Culturally Responsive Teaching (CRT) approach assisted by picture series media. The research was initiated due to the limited poetry writing abilities among fifth-grade students at SDN Sumber 5 Surakarta. This research applied Classroom Action Research based on the Kemmis and Taggart model, which was carried out over two cycles. This study involved 12 students from the fifth grade as research subjects. Data collection techniques that were used includes tests and interview. The findings revealed a significant improvement in students’ poetry writing skills, increasing from 33.33% in the pre-cycle to 83.33% by the second cycle. These results suggest that the use of the CRT approach, supported by picture series media, is effective in improving students' ability to write poetry and can serve as an alternative learning strategy that is relevant and engaging for elementary school students.